2007
DOI: 10.1160/th07-02-0150
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor V and thrombophilia: Background and mechanisms

Abstract: Human coagulation factor V (FV) is an essential coagulation protein with functions in both the pro- and anticoagulant pathways. Failure to express and control FV functions can either lead to bleeding, or to thromboembolic disease. Both events may develop into a life-threatening condition. Since the first description of APC resistance, and in particular the description of the so-called factor V(Leiden) mutation, in which a prominent activated protein C cleavage site in FV has been abolished through a mutation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
154
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 166 publications
(157 reference statements)
3
154
0
7
Order By: Relevance
“…This idea is further supported by the very high thrombotic risk observed in patients who are compound heterozygotes for factor V-deficient and FV Leiden alleles (pseudohomozygotes). Despite bearing only one FV Leiden allele (heterozygous), the thrombotic risk in these patients is similar to that of FV Leiden homozygotes, consistent with the notion that a predominant thrombophilic effect of FV Leiden is related to the inability to generate the anticoagulant molecule FV ac [29].…”
Section: Background and Molecular Basis Of Fv Leiden And Activated Prsupporting
confidence: 75%
See 4 more Smart Citations
“…This idea is further supported by the very high thrombotic risk observed in patients who are compound heterozygotes for factor V-deficient and FV Leiden alleles (pseudohomozygotes). Despite bearing only one FV Leiden allele (heterozygous), the thrombotic risk in these patients is similar to that of FV Leiden homozygotes, consistent with the notion that a predominant thrombophilic effect of FV Leiden is related to the inability to generate the anticoagulant molecule FV ac [29].…”
Section: Background and Molecular Basis Of Fv Leiden And Activated Prsupporting
confidence: 75%
“…Some evidence suggests that the risk of PE is not as great as the risk of DVT in FV Leiden individuals (termed the FV Leiden paradox) [25]. Studies have not consistently shown an increased risk for arterial thrombosis such as myocardial infarction or stroke, although FV Leiden may be more common in affected patients who are young and who have other risk factors such as smoking [26][27][28][29][30].…”
Section: Background and Molecular Basis Of Fv Leiden And Activated Prmentioning
confidence: 99%
See 3 more Smart Citations